Evaluation Of High And Low Grade Ores Of The Point Leamington Massive Sulfide Deposit, Newfoundland - J. M. Melluish (Society for Mining, Metallurgy & Exploration, 1989)
The metallurgical response of the Point Leamington deposit has been studied. Two series of bench tests were conducted and various ore samples and flotation products were examined using image analysis techniques. The majority of sphalerite and chalcopyrite grains in this texturally complex ore were found to be smaller than 10 micrometers. Copper recoveries were low with losses mainly as fine inclusions in pyrite. Sphalerite recoveries were somewhat better due to a generally coarser habit. Gold and silver recoveries were also low and only solid solution silver was identified in the ore. The deposit shows poor economic prospects unless additional tonnage of high grade zinc ore can be delineated.